2019
DOI: 10.1515/jgth-2018-0176
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolic structures on wreath products

Abstract: The study of the poset of hyperbolic structures on a group G was initiated in [1]. However, this poset is still very far from being understood and several questions remain unanswered. In this paper, we give a complete description of the poset of hyperbolic structures on the lamplighter groups Z n wr Z and obtain some partial results about more general wreath products. As a consequence of this result, we answer two open questions regarding quasi-parabolic structures from [1]: we give an example of a group G wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(33 citation statements)
references
References 10 publications
1
32
0
Order By: Relevance
“…The inequality (7) also implies that G Γ ∼ w G S. Taking X ∈ σ([G Γ]) and applying Proposition 3.12 completes the proof.…”
Section: Cobounded Actions and The Svarc-milnor Mapmentioning
confidence: 72%
See 1 more Smart Citation
“…The inequality (7) also implies that G Γ ∼ w G S. Taking X ∈ σ([G Γ]) and applying Proposition 3.12 completes the proof.…”
Section: Cobounded Actions and The Svarc-milnor Mapmentioning
confidence: 72%
“…Define a map φ : Γ → S as follows: for each vertex u of Γ, let φ(u) = u, and for each edge e of Γ, let φ(e) be a geodesic in S from φ(e − ) to φ(e + ). Then (7) implies that φ is a quasi-isometric embedding, and so by [19, Theorem III.H.1.9], Γ is hyperbolic.…”
Section: Cobounded Actions and The Svarc-milnor Mapmentioning
confidence: 99%
“…Nonetheless, significant progress has recently been made in describing the cobounded hyperbolic actions of families of classically studied solvable groups. The second author initiated this study by giving a complete description of the cobounded hyperbolic actions of the lamplighter groups (Z/nZ) Z for n ≥ 2 in [5]. The first and third authors then completely described the hyperbolic actions of Anosov mapping torus groups in [4] and the hyperbolic actions of solvable Baumslag-Solitar groups in [3].…”
Section: Introductionmentioning
confidence: 99%
“…The first two authors and Osin showed in [1] that the set H(G) of equivalence classes of cobounded hyperbolic actions of a group G admits a partial order, which roughly corresponds to collapsing equivariant families of subspaces to obtain one hyperbolic action from another (see Section 2 for the precise definition). Each of the papers [5], [3], and [4] gives a complete description of the poset H(G) for the group G in question.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation